Synthesis of β-Cyclodextrin-Functionalized Silver Nanoparticles and Their Application for Loading Cytisine and Its Phosphorus Derivative - Serik D. Fazylov; Oralgazy A. Nurkenov; Zhangeldy S. Nurmaganbetov; Akmaral Zh. Sarsenbekova; Ryszhan Ye. Bakirova; Olzhas T. Seilkhanov; Alexandr K. Sviderskiy; Ardak K. Syzdykov; Anel Zh. Mendibayeva (Molecules)
In this study, the synthesis and properties of β-cyclodextrin-functionalized silver nanoparticles and their loading with a drug component are considered. β-Cyclodextrin was used as a reducing agent and stabilizer in the preparation of silver nanoparticles. The use of β-CD-AgNPs in loading molecules of the alkaloid cytisine (Cz) and its O,O-dimethyl-N-cytisinilphosphate (CzP) derivative, which have pronounced antiviral properties, was studied. The formation of β-CD-Cz-AgNPs and β-CD-CzP-AgNPs was confirmed by UV spectroscopy and X-ray diffraction spectroscopy. Scanning electron microscopy and transmission electron microscopy showed that the obtained β-CD-Cz-AgNP and β-CD-CzP-AgNP nanocomposites were well dispersed with particle sizes in the range of 3–20 nm. 1H-, 13C-NMR and COSY, HMQC, HMBC and Fourier transform infrared spectroscopy revealed the reduction and encapsulation of AgNPs by β-Cz, and the TEM imaging results showed an increase in the size of nanoparticles after the introduction of cytisine and its phosphorus derivative. The kinetic parameters of the thermal degradation process of β-CD, Cz, CzP and their inclusion complexes Cz(CzP)-β-CD-AgNPs under isothermal conditions, which ensure the preservation of the kinetic triplet, were determined. The differences in the mechanism of thermal decomposition of the studied materials are described by the parameters of the Šesták–Berggren model (m and n), which demonstrated differences for different compounds: for β-CD, the values of the parameters m and n are 0.47 and 0.53, respectively, while for CzP-β-CD-AgNPs they reach values of 0.66 and 1.34. These results indicate differences in the mechanism of thermal decomposition of the studied materials.